Efektivitas Penggunaan Aplikasi Sistem Keuangan Desa (SISKEUDES) Sebagai Bentuk Transparansi dan Akuntabilitas Keuangan Desa Ngoro Kecamatan Ngoro Kabupaten Jombang - Mardani Fitria Ningrum; Moh. Amin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2023)
The central government requires the village government to make APBDes reports and reports on the realization of APBDes implementation as a form of accountability for the performance of village apparatus to the community or the public which is useful for measuring the results of village government performance and is a form of transparency, accountability in the financial reports of Ngoro Village. The purpose of this study is to find out how effective the use of the Village Financial System Application is as a form of transparency and accountability in the financial reports of Ngoro Village, Ngoro District, Jombang Regency. This research uses a qualitative method with a qualitative descriptive research type. The results of this study indicate that the use of the Village Financial System Application has been effective as a form of transparency and accountability in the financial reports of Ngoro Village, Ngoro District, Jombang Regency. Keywords: Transparency, accountability, effectiveness, SISKEUDES